PERAN PROBIOTIK DALAM MENGURANGI RESIKO BAKTERIAL VAGINOSIS DAN KETIDAKSUBURAN PADA WANITA USIA REPRODUKTIF - Andriani, Eka Safitri; Ernawati (Jurnal Medicare, 2025)
This study examines the role of probiotics, especially Lactobacillus strains, in reducing the risk of bacterial vaginosis (BV) and infertility in women of reproductive age. BV occurs due to an imbalance in the vaginal microbiota, characterized by a decrease in Lactobacillus and an increase in pathogenic bacteria, which negatively impacts reproductive health. Probiotics help restore microbiota balance, lower vaginal pH, and protect against infection and inflammation. Findings indicate that probiotics can enhance treatment effectiveness, reduce recurrence, and potentially lower the risk of infertility. However, further research is needed to uncover molecular mechanisms and direct effects on fertility.